A case report of successful treatment of necrotizing fasciitis using negative pressure wound therapy. Issue 2 (January 2019) - de Paula, Fabiana Martins; Pinheiro, Edivania Anacleto; Oliveira, Vanessa Marcon de; Ferreira, Cristiane Munaretto; Monreal, Maria Tereza Ferreira Duenhas; Rolan, Marisa Dias; Matos, Vanessa Terezinha Gubert de
Abstract: Rationale: Necrotizing fasciitis is a destructive tissue infection with rapid progression and high mortality. Thus, it is necessary that high-performance dressings be introduced as possibilities of treatment. Patient concerns: Female patient, 44 years of age, admitted to hospital unit complaining of lesion in the gluteal region and drainage of purulent secretion in large quantity followed by necrosis. Diagnoses: The diagnosis of necrotizing fasciitis was carried out with the computerized tomography examination result and its association with the patient's clinical condition. Interventions: Initially, successive debridements were carried out in lower limbs as well as primary dressing with enzymatic debriding action until indication of negative pressure wound therapy, for the period of 2 weeks in the right lower limb and for 5 weeks in the left lower limb, with changes every 72 h. Dressing with saline gauze was used at the end of this therapy until hospital discharge. Outcomes: After the use of negative pressure wound therapy, we observed the presence of granulation tissue, superficialization and reduction of lesion extension. The patient presented good tolerance and absence of complications. Lessons: Negative pressure wound therapy constituted a good option for the treatment of necrotizing fasciitis, despite the scarcity of protocols published on the subject.